Cold Atmospheric Plasma for Partial-Thickness Burns: Faster Epithelialization and Less Pain with Modern Dressings: A Randomized Clinical Trial - Choi Ji A; Kim Seo Yun; Lee Min Jun (Journal of Wound Research and Technology, 2025)
Background: Partial-thickness burns remain a substantial clinical and service burden, with wide variation in practice and outcomes across settings. Evidence for cold atmospheric plasma (CAP) as an adjuvant to modern dressings is promising but limited, and its effects on healing trajectories and pain in acute burns are not well-defined. Purposes: This study aimed to test whether adding CAP to modern dressings accelerates wound healing and reduces procedural pain compared with dressings alone among adults with second-degree burns. Methods: In a two-arm, assessor-blinded randomized trial at Donghae Dong-in Hospital, Republic of Korea (February–March 2025), adults ≥18 years with partial-thickness burns presenting within 72 hours were randomized to CAP + modern dressing or dressing alone. Forty-one were randomized; 36 contributed to the primary analysis. CAP was applied 3×week for 5–8 minutes before dressing placement. The primary outcome was the percent change in wound area over 28 days. Secondary outcomes were time to complete epithelialization and pain during dressing change (VAS 0–10). Analyses used GLM repeated-measures ANCOVA (covariates: %TBSA, age) and Cox regression. Results: Among 36 analyzed participants (balanced baseline; median %TBSA 5%), CAP accelerated wound-area reduction versus control (Group×Time p<0.001; ηp²=0.25). By Day 28, CAP achieved a 17% greater reduction (adjusted Δ -17%, 95% CI −23 to −11). Pain declined faster with CAP (adjusted Δ −1.5 at Day 14; -1.9 at Day 28). Time to complete epithelialization was shorter with CAP (median 14 vs 21 days; adjusted HR 2.12, 95% CI 1.12–4.01). Effects were directionally consistent across prespecified sensitivity analyses. Conclusion: Adding CAP to modern dressings improved healing trajectories, reduced procedural pain, and shortened time to epithelialization in adults with partial-thickness burns. Findings support protocolized adoption in capable units and motivate multicentre trials with scar, microbiological, and economic endpoints.